Verification of the Canadian Laboratory Initiative on Paediatric Reference Intervals (CALIPER) reference values in Croatian children and adolescents - Zrinski Topić, Renata (Array, 2020)
Introduction: The aim of this study was to examine whether the Canadian Laboratory Initiative on Paediatric Reference Intervals (CALIPER) couldbe applied to Croatian children and adolescents.Materials and methods: A total of 295 outpatient healthy children and adolescents of age 1 to 18 were selected using the direct a posteriorisampling method. According to current guidelines, 20 samples were tested for each of a total of 51 reference intervals for ferritin, cortisol, dehydroepiandrosteronesulfate, follicle stimulating hormone, lutein stimulating hormone, prolactin, progesterone, sex hormone binding globulin, thyroidstimulating hormone, total testosterone, total thyroxine and total triiodothyronine. Serum samples were analysed on the Beckman Coulter DxI600immunoassay analyser by chemiluminescence immunoassay method. A reference interval was adopted if <10% of the results fall outside CALIPERreference interval range. For analytes in which this criterion is not met in the first set of samples, a new set of 20 samples were collected.Results: After the first set of measurements, 96% of all tested reference intervals were adopted for use. The additional sets of 20 reference subjectswere tested for only two reference intervals; follicle stimulating hormone for female aged 1 to 9 years, and irrespective of the gender, sex hormonebinding globulin for children aged 8 to 11 years. All results of additional samples were within the specified interval limits.Conclusions: CALIPER reference intervals for ferritin and 11 hormones defined for Beckman Coulter DxI600 immunoassay analyser can be implementedinto the Croatian laboratories and clinical practice.